Coded Phase Gradient Metasurface Antenna Design for X- Band Radar - Nayak, Monalisa; Jena, Devika; Dhar Sa, Kodanda; Dash, Dillip (International Journal of Computer Sciences and Engineering, 2019)
To achieve long distance coverage and better resolution, high gain antennas is convenient for airborne radars. So a great deal of attention has been devoted to exploiting new approaches towards the problem. Radar application demands a low profile, minimal weight and high gain antennas. Over the last decade microstrip antennas are used as an alternative element for the bulky and heavy weight reflector antennas. Presently researchers are implementing metasurface antennas and their imitative for the radar applications. A high gain transmitting microstrip lens antenna is presented by putting a layered phase gradient coded metasurface with 0 & 1 elements for 0 and π phase responses. Four types of unit cell with two bits coding elements 00,01,10,11 is implemented for four phase differences. The lens antenna results a gain enhancement of 11.7 dbi and return loss of -34 dB, which is approximately 7 dbi and -17dB in case of a normal microstrip antenna, so the gain is enhanced by 4.7dB and a return loss is reduced by 17 dB at 10.3 MHz frequency.